The Transformation of Human Interaction in the Digital Era: A Literature Review on Psychological Impacts and Adaptive Strategies in Communication Psychology - Fiqih, Muhammad; Nurhidayah, Yayah; Ratnawati, Etty (CV. Strata Persada Academia, 2025)
This study examines the transformation of human interaction in the digital era, emphasizing its psychological impacts and adaptive strategies within the framework of communication psychology. The rapid expansion of digital technologies during the Fourth Industrial Revolution—such as social media, instant messaging, and virtual platforms—has facilitated unprecedented connectivity while simultaneously generating significant challenges, including the erosion of non-verbal communication depth, algorithm-driven echo chambers, and pressures associated with digital identity construction. These dynamics have profound implications for empathy, emotional regulation, and self-concept stability, particularly among adolescents and young adults. Using a descriptive qualitative approach through a systematic literature review, this research synthesizes recent scholarly findings from accredited journals, books, and conference proceedings. The results underscore the necessity of adaptive communication psychology strategies focusing on emotional literacy, self-awareness, and positive online behavior to promote healthier digital interactions. The study recommends integrating these strategies into formal and non-formal education to foster digital resilience and mitigate adverse psychological outcomes. Future research should explore culturally sensitive interventions to enhance social cohesion and psychological well-being in increasingly digital societies.